Microtomographic Assessment of the Shaping Ability of the Hyflex CM and XP-endo Shaper Systems in Curved Root Canals - Dantas, Wania Christina Figueiredo; Marceliano-Alves, Marilia Fagury Videira; Marceliano, Eduardo Fagury Videira; Marques, Eduardo Fernandes; de Carvalho Coutinho, Thais Machado; Alves, Flavio R.F.; Martin, Alexandre Sigrist De; Pelegrine, Rina Andrea; Lopes, Ricardo Tadeu; Bueno, Carlos Eduardo da Silveira (European Journal of Dentistry, 2022)
Objective This study compared the shaping ability of the Hyflex CM and XP-endo Shaper rotary file systems in curved mesial canals of mandibular molars using micro-computed tomography.Material and Methods Seventeen mesial roots of extracted first mandibular molars with two independent mesial canals were scanned before and after root canal preparation with the tested rotatory file systems. Each mesial canal from the same specimen was prepared with one of the two systems. The parameters analyzed were canal centering (transportation) for the cervical, middle, and apical segments, as well as for the entire canal (0–10 mm from the apex); and canal volume increase, canal surface area increase, and unprepared canal walls for two segments, 0 to 4 mm and 0 to 10 mm from the apex.Results There was no significant difference between both systems regarding canal centering (transportation), volume increase, and unprepared canal walls for the 0 to 10 mm segment (p> 0.05); however, a significant difference was observed for the 0 to 4 mm segment (p <0.01), where the Hyflex CM left 28.46% of unprepared walls and XP-endo Shaper left 13.26%.Conclusions The shaping ability of the two tested rotatory file systems in mesial roots of first mandibular molars was similar for all parameters in all the segments evaluated, except for the 0 to 4 mm segment, where XP-endo Shaper left a smaller area of unprepared canal walls than Hyflex CM.
Keywords: root canal therapy; microtomographic analysis; unprepared canal walls; rotary instruments; Hyflex CM; XP-endo Shaper; curved canals